2014
DOI: 10.2147/ijn.s61779
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of silver nanoparticles using Acacia leucophloea extract and their antibacterial activity

Abstract: The immense potential of nanobiotechnology makes it an intensely researched field in modern medicine. Green nanomaterial synthesis techniques for medicinal applications are desired because of their biocompatibility and lack of toxic byproducts. We report the toxic byproducts free phytosynthesis of stable silver nanoparticles (AgNPs) using the bark extract of the traditional medicinal plant Acacia leucophloea (Fabaceae). Visual observation, ultraviolet–visible spectroscopy, and transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 22 publications
2
31
0
Order By: Relevance
“…Thus, the particles might aggregate and flocculate due to the absence of a repulsive force. It was also observed that there was the presence of some weak peaks at 28°, 54°, 57° and 86° which might have been from the organic compound in the leaf extract (Figure 4) [21,22]. A study showed that in the biosynthesis of AgNPs by the reduction of Ag ions, the terpenoids in the leaf extract play a crucial role [19].…”
Section: Characterization Of Synthesized Silver Nanoparticlesmentioning
confidence: 98%
“…Thus, the particles might aggregate and flocculate due to the absence of a repulsive force. It was also observed that there was the presence of some weak peaks at 28°, 54°, 57° and 86° which might have been from the organic compound in the leaf extract (Figure 4) [21,22]. A study showed that in the biosynthesis of AgNPs by the reduction of Ag ions, the terpenoids in the leaf extract play a crucial role [19].…”
Section: Characterization Of Synthesized Silver Nanoparticlesmentioning
confidence: 98%
“…These compounds act as reducing and stabilizing agents of the AgNPs. Interestingly, plants have the incredible ability to enclose nanoparticles, forming a membrane around them and stopping the nanoparticles from forming aggregates, and in doing so stabilize the solution [20].…”
Section: The Bark Of Woody Vascular Plants—a Source Of Phytoconstimentioning
confidence: 99%
“…Metal-based NPs have a broad antibacterial effect on a range of gram-negative and -positive bacteria and antibiotic-resistant bacteria strains (Ge et al, 2014). Although Ag NPs alone are strong bactericidal agents (Murugan et al, 2014), they are also cytotoxic (Ge et al, 2014). Embedding them in a polymer matrix may reduce their cytotoxicity (Liu et al, 2010).…”
Section: Unique Physical and Chemical Properties Of Nanomaterialsmentioning
confidence: 99%